O uso de imagens mentais por cantores líricos como recurso técnico na colocação vocal - Cruz, Tâmara de Oliveira (2016)
This research aimed to investigate the role of mental imagery on teaching and vocal placement domain in lyrical singers. Our first methodological approach consisted in bibliographic research, through which we could observe the importance the resource of mental imagery occupies in human activities as whole, being increasingly scientifically approached in several areas of knowledge; we noted, likewise, the way the issue of vocal placement has been approached in methods, treaties, books and articles since 18th century to nowadays. Afterwards, we used another method, the field research as semi-structured interview, which was applied to seven lyrical singers in different stages of formation and practice, who professionally act such as singers and singing teachers. We aimed to understand the peculiar views of each interviewed about the use of the mental imagery on their activities as singers and teachers, focusing on vocal placement. We concluded that mental imagery are considered an important technical and didactic resource, widely disseminated and accepted among singers and singing teachers as regards vocal placement. We verified, likewise, that these activities are widely supported by the literature, where we can find many studies about the relationship between mental imagery and many aspects of classical singing.